Performance of Jute Fabric-Reinforced Polymer Concrete as Permanent Formwork - Shyue, Leong Lee; Mohammad, Abdul Mannan; Ivonson, Kwee; Chiang, Chong Kian (Springer, 2021)
This research was conducted to investigate the potential use of jute fabric-reinforced polymer concrete as permanent formwork for building structures. The performance of Portland cement concrete, polymer concrete, and jute fabric-reinforced polymer concrete was investigated through compressive and flexural strengths and deflection. In addition, composite beams (Portland cement concrete cast on top of jute fabric-reinforced polymer concrete as permanent formwork) were prepared and tested for flexural strength and measured for deflection. The result indicated that composite beam had higher flexural strength compared to Portland cement concrete. Moreover, in actual practice, there would be a connection between the permanent formworks as compared to laboratory-prepared composite beams. So, two different connection gaps and connection angles were proposed, respectively. The results showed that the connection gap and connection angle had an effect on the flexural strength and deflection. Overall, the potential use of jute fabric-reinforced polymer concrete as permanent formwork was determined.